Karakterisasi dan Toksisitas Akut pada Minyak Buah Merah - Widowati, Lucie; Pudjiastuti, Pudjiastuti; Mudahar, Harfia (Jurnal Kefarmasian Indonesia, 2009)
Buah Merah (Pandanus conoideus Lam), is an endemic plant from Papua and its surrounding. Oil of buah merah known and claimed for cancer, HIV/AIDS, lung tuberculosis, diabetic and decreased blood cholesterol treatment. Since buah merah oil widlly is used in communities, safety test is needed. There were no toxic effects as abnormal behavior or mortality in rats, even using in high dose of 5 ml/200g body weight or approximately 9.4 times of human dose (1 x HD = 30 ml). Due to this situation, the acute toxicity has been done by Biomedical and Pharmaceutical Research and Development Center, at 2006. The result showed that qualitative test based on chemical group compounds, triterpenoid, phenol and steroid have been found clearly. Basically the oil is not toxic for single dose. Since there ‘s no mortality, the LD;0 will be considered as pseudo LD50, that means that doses of 5 ml/200g body weight of Wistar rat is safe for utilization, or the safety dose for human will bein a very large range.